2014
DOI: 10.3906/tar-1312-108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plasma treatment and sanding process on surface roughness of wood veneers

Abstract: An ideal veneer surface is crucial for good panel properties in plywood manufacturing. The aim of this study was to compare plasma treatments and sanding (mechanical) processes with respect to the surface roughness of veneers. Rotary-cut veneers with a thickness of 2 mm from Scots pine (Pinus sylvestris) logs were used as material. After rotary peeling, veneer sheets were dried at 110 °C in a veneer dryer. Veneer sheets were divided into 4 main groups. The surfaces of the control veneer sheets were left untrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…A reflection structure image of high-gloss composite products was developed as an alternative method to describe the visual human perception of gloss [3]. However, recent studies have shown off the comfortable feelings given by both the coated and uncoated surfaces of wood products [4,5]. A model based on the value generation of wooden furniture has been validated by these qualitative, innovative, and ecological products.…”
Section: Introductionmentioning
confidence: 99%
“…A reflection structure image of high-gloss composite products was developed as an alternative method to describe the visual human perception of gloss [3]. However, recent studies have shown off the comfortable feelings given by both the coated and uncoated surfaces of wood products [4,5]. A model based on the value generation of wooden furniture has been validated by these qualitative, innovative, and ecological products.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the plasma modification process has been used to modify the surfaces of wood and wood based materials in order to enhance surface properties of the wood component and mechanical strength of the wood based materials (Aydin and Demirkir 2010, Acda et al 2012, Demirkir et al 2014.Plasma treatment is used to improve bonding properties of many materials such as wood based products by altering the surface properties and chemical structure of the wooden components. Bond quality as one of the most important parameters in wood based panels depends on the intermolecular attraction between the adhesive and the wood components.…”
Section: Introductionmentioning
confidence: 99%
“…Obdelava lesa in lesnih kompozitov s plazmo predstavlja enega od načinov za spremembo lastnosti površin (Wolkenhauer et al, 2008;Demirkir et al, 2014), na katere lahko z namenom povečanja površinske zaščite materiala nanesemo različne premaze (Riedl et al 2014). Do sedaj je bilo veliko raziskav izvedenih na temo obnašanja tekočin na tako modificiranih površinah, v smislu merjenja kontaktnih kotov in določanja proste površinske energije s plazmo obdelanih površin lesa Wolkenhauer et al, 2015).…”
Section: Uvod / Intruductionunclassified